(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides an in-depth exploration of the significance and evolution of titles in literary texts. Drawing from historical, linguistic, and literary perspectives, it illustrates the origins of titles, their various functions, and their typologies. The article discusses how titles have transitioned from mere identifiers to complex entities that frame readers’ expectations, convey themes and ideas, and shape the overall reading experience. Additionally, the article emphasizes the diversity of title forms and their impact on attracting attention, evoking curiosity, and conveying emotional and conceptual content. Overall, it offers a comprehensive analysis of the multifaceted nature of titles and their pivotal role in literary interpretation and appreciation.